An analysis of biodiversity of Bach Long Vi island, Hai Phong city - Quang, Bui Duc; Quynh, Ha Quy (Academia Journal of Biology, 2014)
Bach Long Vi Island is located in the centre of Tonkin Gulf, Hai Phong City, Northeastern Vietnam. The island plays an important role in sea management, economic development, national security of Vietnam. On the other hand, it houses one of the eight important fisheries within the Tonkin Gulf. This paper presents an overview of diversity of plants and annimals recorded from the island with reference to its natural features including geo-topography, climate, and hydrology. In general, Bach Long Vi and its surroundings contains terrestrical and coastal ecosystems. To date, it is known as a home to a variety of species comprising 281, 74, 16, 15 and 5 species of vascular plants, birds, mammals, reptiles and amphibians, respectively. Considerably, number of fish species (451) of Bach Long Vi is greater than that of Cat Ba (196) and Co To islands (191) while numbers of species belonging to phytoplankton, zooplankton, zoobenthod, seaweed, and coral of Bach Long Vi are less than those of Co To and Cat Ba islands.